2015
DOI: 10.4269/ajtmh.14-0396
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Assessments of the Strength of Program Implementation for Community Case Management of Childhood Illness: Validation of a Mobile Phone-Based Method in Malawi

Abstract: Health surveillance assistants (HSAs) in Malawi have provided community case management (CCM) since 2008; however, program monitoring remains challenging. Mobile technology holds the potential to improve data, but rigorous assessments are few. This study tested the validity of collecting CCM implementation strength indicators through mobile phone interviews with HSAs. This validation study compared mobile phone interviews with information obtained through inspection visits. Sensitivity and specificity were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…The quality of data produced by Health Management Information Systems—even when these systems include relevant data points—is often unknown and records are universally suspected to be incomplete. 3 New and complementary methods are needed to produce up-to-the-moment snapshots of implementation strength for use in improving health service provision, calibrating routine monitoring systems, and interpreting changes (or lack of change) in measures of program outcome and impact.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of data produced by Health Management Information Systems—even when these systems include relevant data points—is often unknown and records are universally suspected to be incomplete. 3 New and complementary methods are needed to produce up-to-the-moment snapshots of implementation strength for use in improving health service provision, calibrating routine monitoring systems, and interpreting changes (or lack of change) in measures of program outcome and impact.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the IC kept more records of these indicators than the HSAs and CBDAs. Similar studies, such as Hazel et al, demonstrated higher sensitivity and specificity largely because they evaluated a very specific program that had been recently implemented with clear, measurable components [14]. The ISA used for this study was much broader, as it aimed to assess multiple FP programs implementing a wider set of FP practices.…”
Section: Discussionmentioning
confidence: 89%
“…The rapid increase in mobile phone ownership and network availability in lower income countries could offer an alternative, cost-effective avenue to collect data for a better understanding of program implementation. However, there is still uncertainty about the validity and feasibility of remote data collection in lower income countries, especially among health workers [14,31]. This study tests whether using this m-Health method can produce valid IS data and can this be a feasible alternative to traditional data collection methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, the diagnosis and treatment of childhood illness in developing countries has received immense attention (Hazel et al, 2015). The underlying rationale for this increased awareness may stem from the establishment of the eight Millennium Development Goals by the United Nations in 2001, more specifically the fourth goal which focuses on reducing under-five child mortality rates in developing countries.…”
Section: Introductionmentioning
confidence: 99%